Electrochemical determination of antimalarial drug amodiaquine in maternal milk using a hemin-based electrode - Valente, Cristiane O.; Garcia, Carlos A. B.; Alves, José P. H.; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Arguelho, Maria Lara P. M. (The Electrochemical Society, 2012)
Voltammetric analysis of amodiaquine using a hemin biosensor revealed a well-defined peak at 0.14 V (vs. Ag/AgCl), corresponding to the oxidation of amodiaquine at pH 7.0. The electrodic behavior indicated that the oxidation process was irreversible, and that it was controlled by diffusion. In addition to advantages such as high selectivity and sensitivity, the method developed could be used for the analysis of breast milk containing amodiaquine without any need for prior sample treatment, an important consideration in routine analysis laboratories. Measurements of the drug contained in breast milk were used to validate the technique. The detection limit for standard solutions was 3.30 mg L-1, and the quantification limit was 11.0 mg L-1. ©The Electrochemical Society.
Keywords: Antimalarial drug; Detection limits; Electrochemical determination; Oxidation process; Quantification limit; Routine analysis; Standard solutions; Voltammetric analysis; Biosensors; Electrochemistry; Chemical detection